Intact FGF23 and α‐klotho during acute inflammation/sepsis in CKD patients. (21st January 2016) - Dounousi, Evangelia; Torino, Claudia; Pizzini, Patrizia; Cutrupi, Sebastiano; Panuccio, Vincenzo; D'Arrigo, Graziella; Abd ElHafeez, Samar; Tripepi, Giovanni; Mallamaci, Francesca; Zoccali, Carmine
Abstract: Background: High FGF23 and low α‐Klotho levels associate with systemic inflammation and reduced nitric oxide (NO) bioavailability, but the dynamics of this relationship in patients with CKD has not been investigated. Methods: We sequentially measured serum intact FGF23 and carboxyl‐terminal (iFGF23, cFGF23), the iFGF23/cFGF23 ratio, αKlotho, biomarkers of inflammation (hs‐CRP, IL‐6 and TNF‐α) and sepsis (procalcitonin), nitrotyrosine (reflecting NO synthesis and oxidative stress), serum iron and ferritin and CKD‐MBD biomarkers, PTH, 25(OH)VD, 1, 25(OH)2 VD at peak of intercurrent sepsis and after complete resolution in a series of 17 patients with CKD. Results: At peak infection, biomarkers of inflammation/sepsis, ferritin and nitrotyrosine were all very high (all P < 0·01) and declined towards the normal range thereafter ( P < 0·01). iFGF23 was 191 ± 10 pg/ml (geometric mean, SD) and doubled to 371 ± 8 pg/ml ( P = 0·003) after the resolution of infection, while cFGF23 did not change (246 ± 5 pg/mL vs. 248 ± 5 pg/mL, P = 0·50). As a consequence, the iFGF23/cFGF23 ratio, an indicator of the proteolytic cleavage of the FGF23 molecule, was 0·78 ± 3·87 at peak infection and increased to 1·49 ± 3·00 after resolution of infection ( P < 0·001). In contrast, serum α‐Klotho levels were upregulated at peak infection (peak infection: 526 ± 4 pg/ml, postinfection: 447 ± 4 pg/ml, P = 0·001). The eGFR, PTH and vitamin D did not change significantly throughout. Conclusions: Acute inflammation/sepsis suppresses the active form of FGF23 and activates α‐Klotho, the latter effect being likely attributable to enhance proteolysis of FGF23 molecule. iFGF23 downregulation and α‐Klotho upregulation during acute sepsis may participate into the counter‐regulatory response to severe inflammation in CKD patients with sepsis.